Adobe After Effects Classroom in a book 2024 release : the official training workbook from Adobe - Gyncild, Brie; Fridsma, Lisa (Adobe Press, 2024)
Adobe After Effects Classroom in a Book uses real-world, project-based learning to cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. For beginners and experienced users alike, you can follow the book from start to finish or choose only those lessons that interest you.
Includes index
Keywords: Adobe After effects; Cinematography -- Special effects -- Data processing; Computer animation -- Software -- Handbooks, manuals, etc; Image processing -- Digital techniques; Computer graphics; Multimedia systems; Cinéma; Effets spéciaux; Informatique; Animation par ordinateur; Logiciels; Guides, manuels, etc; Traitement d'images; Techniques numériques; Infographie; Multimédia; digital imaging; computer graphics